Effect of Jagged1 on the expression of genes in regulation of osteoblast differentiation and bone mineralization ontology in human dental pulp and periodontal ligament cells - Kanokporn Hansamuit; Thanaphum Osathanon; Jaijam Suwanwela (Elsevier, 2020)
Objective: To define the effect of Jagged1 on the gene expression in osteoblast differentiation, regulation of osteoblast differentiation and regulation of bone mineralization ontology. Methods: Human dental pulp and periodontal ligament cells were isolated using explant method. Cells were seeded on Jagged1 immobilized surface. The mRNA expression was determined using real-time polymerase chain reaction. Mineral deposition was evaluated using alizarin red s staining. Publicly available database of gene expression profiles (GSE126249 and GSE94989) were downloaded and performed bioinformatic analysis to identify gene expression in osteoblast differentiation and regulation of osteoblast differentiation and mineralization ontology. Results: Both human dental pulp cells and human periodontal ligament cells expressed higher Notch target gene (HES1 and HEY1) when cells were seeded on Jagged1 immobilization surface. Jagged1 significantly increased an in vitro mineral deposition in both cell types after maintaining in osteogenic induction medium for 14 days. Correspondingly, the significant increase of ALPL mRNA expression was observed, while there was no significant change in ANKH and ENPP1 mRNA expression in Jagged1 treated condition. From bioinformatic analysis of genes in osteoblast differentiation ontology, IARS, COL1A1, ALPL, COL6A1, CREB3L1, and SNAI2 mRNA levels were upregulated while GJA1 mRNA levels were decreased upon Jagged1 exposure. In the regulation of bone mineralization ontology, evidences supported that TFGB1 and TGFB3 were upregulated in Jagged1 treated condition. Conclusion: Jagged1 promote the mRNA expression of several genes in osteoblast differentiation related gene ontology. This could be further employed to identify the mechanism by which Jagged1 promoted osteogenic differentiation in human dental pulp and periodontal ligament cells.